Entrepreneurship in India - Newman, Alexander (Professor of management) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The economic liberalization in India over the last three decades has provided a wealth of opportunity for entrepreneurs looking to start and expand their businesses. Since the economy opened up in the 1990s, entrepreneurial activity in the private sector has been largely responsible for the strong economic growth experienced in the country. India is presently the world's third largest source of start-ups, and was ranked the second most entrepreneurial country in the world in the recent Global Entrepreneurship Monitor (GEM) report, ahead of large economic powerhouses such as the United States, China and the UK. Entrepreneurship in India looks at the dynamic and changing nature of entrepreneurship in India. The book examines the history of entrepreneurship in India, different entrepreneurship models adopted, the entrepreneurial ecosystem and looks at the future of entrepreneurship in the country. This book will benefit business people, policy makers and researchers looking to understand more about entrepreneurship in India, and offers guidance to foreign business looking to engage with entrepreneurs in India"--
India's entrepreneurial transformation -- History of entrepreneurship in India -- India's entrepreneurs and private enterprises -- Women's entrepreneurship in India -- Case studies of women entrepreneurs in India -- Financing entrepreneurship in India -- Indian culture and its influence on entrepreneurship -- Dealing with the government -- Doing business with Indian entrepreneurs -- The future of entrepreneurship in India.
Keywords: Entrepreneurship -- India; Small business -- India; Businesspeople -- India; BUSINESS & ECONOMICS / Entrepreneurship